2013
DOI: 10.1021/ol4030937
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Cassaine Utilizing an Anionic Polycyclization Strategy

Abstract: A stereoselective total synthesis of (+)-cassaine (1) via an anionic polycyclization methodology is described. Commercially available (+)-carvone (5), the only chiral source, was used to fix the entire stereochemistry of the natural product. Anionic polycyclization of a new substituted 2-(methoxycarbonyl)cyclohex-2-en-1-one (4) with known 1-phenylysulfinyl-3-penten-2-one (3) provided the versatile tricycle (2) with requisite stereochemistry. A sequence of functional group manipulations of tricycle (2) furnishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(33 reference statements)
1
16
0
3
Order By: Relevance
“…[186] First the reaction of (+)-carvone with EVK 52 under usual conditions furnishes the known 6-epi-αcyperone. A series of functional group transformations yields a β-keto ester 317 which readily reacts with the Nazarov reagent 318 under slightly basic conditions.…”
Section: Nazarov Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[186] First the reaction of (+)-carvone with EVK 52 under usual conditions furnishes the known 6-epi-αcyperone. A series of functional group transformations yields a β-keto ester 317 which readily reacts with the Nazarov reagent 318 under slightly basic conditions.…”
Section: Nazarov Reagentsmentioning
confidence: 99%
“…Thes ynthesis of (+ +)-cassaine is interesting as it features two different annulation strategies (Scheme 89). [186] First, the reaction of (+ +)-carvone with EVK (52)u nder the usual conditions furnishes the known 6-epi-a-cyperone.Aseries of functional-group transformations yields the b-keto ester 317, which reacts readily with the Nazarov reagent 318 under slightly basic conditions.T his particular method allows the formation of as ingle diastereoisomer of the requisite stereochemistry (axial C14 methyl group), as implied by the configuration of the angular methyl group at C10.…”
Section: Nazarov Reagentsmentioning
confidence: 99%
“…An elegant anionic polycyclization strategy of Deslongchamps et al led to the total synthesis of (+)-cassaine ( 23 ) as shown in Scheme 3 [ 18 ]. (+)-Cassaine was isolated from Erythrophleum guineense in 1935 and reported as a nonsteroidal Na + -K + -ATPase inhibitor [ 19 ].…”
Section: Anionic Cyclizationsmentioning
confidence: 99%
“…[186] Zuerst wurde durch Reaktion von (+ +)-Carvon mit EVK (52) unter normalen Bedingungen das bekannte 6-epi-a-Cyperon erhalten. [186] Zuerst wurde durch Reaktion von (+ +)-Carvon mit EVK (52) unter normalen Bedingungen das bekannte 6-epi-a-Cyperon erhalten.…”
Section: Nazarov-reagentienunclassified
“…Die Synthese von (+ +)-Cassain umfasst interessanterweise zwei verschiedene Anellierungsstrategien (Schema 89). [186] Zuerst wurde durch Reaktion von (+ +)-Carvon mit EVK (52) unter normalen Bedingungen das bekannte 6-epi-a-Cyperon erhalten. Darauf folgte eine Reaktionsreihe zur Umwandlung funktioneller Gruppen, die zum b-Ketoester 317 führte,d er leicht mit dem Nazarov-Reagens 318 unter schwach basischen Bedingungen reagierte.Diese spezielle Methode ermçglichte die Bildung eines einzigen Diastereomers mit der gewünschten Konfiguration (axiale C14-Methylgruppe), die durch die Stellung der Methylgruppe an C10 bestimmt wird.…”
Section: Nazarov-reagentienunclassified